Cover Image, Volume 116, Number 7, July 2019. Issue 7 (1st June 2019) - Turnbull, Jordan; Wright, Bernice; Green, Nicola K.; Tarrant, Richard; Roberts, Iwan; Hardick, Oliver; Bracewell, Daniel G.
Abstract : The front cover image is based on the Article Adenovirus 5 recovery using nanofiber ion‐exchange adsorbents by Jordan Turnbull et al., DOI:10.1002/bit.26972 .